Urban watersheds geology, contamination, and sustainable development - Kaufman, Martin M. (CRC Press, 2011)
"This handbook presents 10 years of research on contaminants affecting lands and waters within heavily urbanized. It integrates research and professional practice from the fields of environmental geology, geochemistry, risk analysis, hydrology, and urban planning and offers knowledge on improving watershed management practices and urban development. It explains different aspects of urban land and water contamination; including sources, extents, and risks. The text includes case studies on successful and unsuccessful approaches to contaminant remediation, as well as practical methods for environmental risk assessment"-- Provided by publisher.
Keywords: Urban runoff -- Management.; Urban watersheds -- Protection.; Water -- Pollution.; Sustainable development.; Cities and towns -- Environmental conditions.; Urban pollution.; elektronické knihy; electronic books